Independent confirmation of global land warming without the use of station temperatures. Issue 12 (17th June 2013) - Compo, Gilbert P.; Sardeshmukh, Prashant D.; Whitaker, Jeffrey S.; Brohan, Philip; Jones, Philip D.; McColl, Chesley
Abstract: [1] Confidence in estimates of anthropogenic climate change is limited by known issues with air temperature observations from land stations. Station siting, instrument changes, changing observing practices, urban effects, land cover, land use variations, and statistical processing have all been hypothesized as affecting the trends presented by the Intergovernmental Panel on Climate Change and others. Any artifacts in the observed decadal and centennial variations associated with these issues could have important consequences for scientific understanding and climate policy. We use a completely different approach to investigate global land warming over the 20th century. We have ignored all air temperature observations and instead inferred them from observations of barometric pressure, sea surface temperature, and sea‐ice concentration using a physically based data assimilation system called the 20th Century Reanalysis. This independent data set reproduces both annual variations and centennial trends in the temperature data sets, demonstrating the robustness of previous conclusions regarding global warming. Key Points: Barometers and ocean data reproduce global land warming Conclusions based on large‐area averages of land temperatures are robust